An atomistic-to-microscale computational analysis of the dislocation pileup-induced local stresses near an interface in plastically deformed two-phase materials. (March 2022) - Peng, Yipeng; Ji, Rigelesaiyin; Phan, Thanh; Gao, Wei; Levitas, Valery I.; Xiong, Liming
Highlights: The microscale dislocation slip together with the atomic-scale process of a step formation at the slip-interface intersection are simultaneously resolved in one single computer model. The internal stress concentration ahead of the slip-interface intersection spans a long range up to hundreds of nanometers when tens of dislocations are piled up at the buried interface. The dislocation pileup-induced stress concentration ahead of the slip-interface intersection deviates from the Eshelby model-based common wisdom which treats interface as rigid. The pileup-induced stress can be largely underestimated if one relies on nanoscale atomistic simulations to correlate the dislocation density with the pileup tip stress intensity factor. Graphical abstract: Abstract: Taking the two-phase material as a model system, here we perform atomistic-to-microscale computational analysis on how the dislocations pileup is formed at a buried interface through two-dimensional concurrent atomistic-continuum simulations. One novelty here is a simultaneous resolution of the μ m-level dislocation slip, the pileup-induced stress complexity, and the atomic-level interface structure evolution all in one single model. Our main findings are: (i) the internal stresses induced by a pileup spans a range up to hundreds of nanometers when tens of dislocations participate the pileup; (ii) the resulting stress concentration decays as a function of the distance, r, away from the pileup tip, but deviates from the Eshelby model-based 1 / r 0.5, where the interface was assumed to be rigid without allowing any local structure reconstruction; and (iii) the stress intensity factor at a pileup tip is linearly proportional to the dislocation density nearby the interface only when a few dislocations are involved in the pileup, but will suddenly "upper bend" to a very high level when tens of or more dislocations arrive at the interface. The gained knowledge can be used to understand how the local stresses may dictate the plastic flow-induced phase transformations, twinning, or cracking in heterogeneous materials such as polycrystalline steel, Ti-, Mg-, high entropy alloys, fcc/bcc, fcc/hcp, and bcc/hcp composites, containing a high density of interfaces.